Lattice distortion and residual stress of a carbon‐doped TiZrN coating. Issue 5 (11th March 2018) - Hong, Eunpyo; Jeon, Seol; Choi, Youngkue; Yoo, Hyunjo; Kwon, Se‐Hun; Lee, Heesoo
Abstract: The mechanism of hardness improvement of a TiZrN coating by carbon doping was investigated in terms of the residual stress and the lattice deformation. Carbon was doped using laser carburization to improve the hardness of TiZrN, which was increased from 3025 HV to 3388 HV. The lattice parameter was calculated through Rietveld refinement in order to analyze the behavior inside the lattice due to carbon doping, which showed that the parameter increased from 4.21 Å to 4.44 Å after the carbon doping process. The diffraction pattern was analyzed using an electron beam to identify the lattice state of the coating layer, and lattice distortion was revealed through a diffused ring pattern. The compressive residual stress was increased by 48%, which was identified through the sin 2 Ψ method using the lattice constant change due to carburization. After the carbon doping, the hardness of the TiZrN was increased by 10%, which was attributed to the expansion distortion generated in the TiZrN lattice and the increase of the compressive residual stress.